1995
DOI: 10.1002/neu.480260409
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring motoneuron cell death in rat upper respiratory tract motor nuclei: A histological, fast dil and immunocytochemical study in the nucleus ambiguus

Abstract: The mammalian upper respiratory tract (URT) serves as the common modality for aspects of respiration, deglutition, and vocalization. Although these actions are dependent on coordinated and specific neuromuscular control, little is known about the development of URT control centers. As such, this study investigated the occurrence of naturally occurring motoneuron cell death (MCD) in the nucleus ambiguus (NA) of a developmental series of rats. Standard histological techniques were used to count motoneurons in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
(55 reference statements)
3
13
0
Order By: Relevance
“…motor nuclei. For example, although several studies have indicated a postnatal period of motoneuron death (Tadaet al, 1979;Rootman et al, 1981;Scarisbrick et al, 1990), others have demonstrated an entirely prenatal course (Lance-Jones, 1982;Oppenheim, 1986;Oppenheim et al, 1986;Friedland et al, 1995). Our findings support the observations of the latter group, suggesting an entirely prenatal time course for the occurrence of MCD in the rodent.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…motor nuclei. For example, although several studies have indicated a postnatal period of motoneuron death (Tadaet al, 1979;Rootman et al, 1981;Scarisbrick et al, 1990), others have demonstrated an entirely prenatal course (Lance-Jones, 1982;Oppenheim, 1986;Oppenheim et al, 1986;Friedland et al, 1995). Our findings support the observations of the latter group, suggesting an entirely prenatal time course for the occurrence of MCD in the rodent.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the findings just given, cell death in XI1 was also lower than the 50% cell death observed in the other URT motor nucleus, NA (Friedland et al, 1995). This difference in the amount of cell death may reflect the relative complexity of the motor nuclei.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations